(untitled) (Bangladesh Journal of Zoology, 2025)
The present study sought to differentiate various sources of Heteropneustes fossilis samples morphologically using two hundred and twenty-five samples from six natural and three hatchery sources in Bangladesh. Eighteen morphometric and five meristic characters were studied, and the analysis highlighted that natural stocks were significantly different from hatchery stocks. The multivariate analysis showed a significant difference (p<0.05) in morphometric features between Asian stinging catfish from natural and hatchery origins such as pectoral fin length (PCFL), pre-anal fin length (PAL), pre-pectoral fin length (PPCL), length of dorsal fin base (LDFB), body width (BW), eye diameter (ED), postorbital (Post OL) as well as meristic characters i.e. caudal fin ray (CFR). Significant differences in morphometric and meristic characteristics were also found using the nonparametric Kruskal-Wallis (H) test. Natural and hatchery sources of H. fossilis strongly differ in standard length (SL) and post-orbital length (Post OL), as identified by principal component analysis. Additionally, the discriminate analysis identified total length (TL), pre-anal fin length (PAL), pre-pectoral fin length (PPCL), and body width (BW) as distinguishing traits. According to hierarchical cluster analysis, there was a minimum divergence between the natural and hatchery sources, and it partially separated the two sources. However, hatchery-originated stinging catfish must be utilized carefully in Bangladesh’s diverse cultural contexts; the current result may help determine if new morphotypes develop from genetic introgression and other causes. Bangladesh J. Zool. 52(3): 281-300, 2024